PERSEPSI PESERTA DIDIK TERHADAP PEMBELAJARAN DIFERENSIASI DALAM MATA PELAJARAN MATEMATIKA - Karwati, Neng Novi; Holis, Ade; Amirudin, Ja'far (Universitas Pendidikan Indonesia Kampus Serang, 2025)
Identifying primary school students’ perception is important for teachers to understand the characteristics and allow them to participate fully in the classroom in the appropriate way that suits students learning style. Differentiated learning potentially create new dynamics that are important for primary school students to perceive. This research uses a quantitative descriptive approach to produce an accurate picture of the students’ perception phenomena and present various related information. Furthermore, this research was involved 4th grade students as research object and carried out at SDIT Atikah Musaddad in the period October to December 2024. The data collection techniques used were observation, interviews, questionnaires and documentation. The results found that students' perceptions of differentiated learning in mathematics subjects showed the average score of respondents in the “Strongly Disagree” category of score 2, the “Disagree” category reached a score of 3, the “Disagree” category reached a score of 53, the “Agree” category reached 488, and the “Strongly Agree” category reached a score of 254. Therefore, students' perception of differentiated learning in mathematics tends to agree. The researcher concluded that differentiated learning has been fully implemented since the existence of an independent curriculum at SDIT Atikah Musaddad school, which is carried out by mathematics teachers, gave good perceptions according to students' experiences when learning is taking place. Students positive perceptions of differentiated learning in mathematics are perceived to improve learning outcomes and learners’ activeness and can make learners feel more independent in learning, and make the learning process more enjoyable. This finding can be used as a foundation for other institutions to develop the implementation of differentiated learning.